2019
DOI: 10.1158/2326-6066.cir-18-0579
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced SLAMF7 Homotypic Interactions by Elotuzumab Improves NK Cell Killing of Multiple Myeloma

Abstract: Elotuzumab (Elo) is an IgG 1 monoclonal antibody targeting SLAMF7 (CS1, CRACC, and CD319), which is highly expressed on multiple myeloma (MM) cells, natural killer (NK) cells, and subsets of other leukocytes. By engaging with FcgRIIIA (CD16), Elo promotes potent NK cell-mediated antibody-dependent cellular cytotoxicity (ADCC) and macrophage-mediated antibody-dependent cellular phagocytosis (ADCP) toward SLAMF7 þ MM tumor cells. Relapsed/refractory MM patients treated with the combination of Elo, lenalidomide, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…Elotuzumab is an IgG 1 mAb that targets signaling lymphocytic activation molecule F7 (SLAMF7), also known as CD319, which is highly expressed on MM, NK and other immune cells (132). Elotuzumab was found to activate NK cells and induce apoptosis of SLAMF7 + cells via both CD16dependent and CD16-independent mechanisms (132,133).…”
Section: Monoclonal Antibodies For Targeting Plasma Cellsmentioning
confidence: 99%
“…Elotuzumab is an IgG 1 mAb that targets signaling lymphocytic activation molecule F7 (SLAMF7), also known as CD319, which is highly expressed on MM, NK and other immune cells (132). Elotuzumab was found to activate NK cells and induce apoptosis of SLAMF7 + cells via both CD16dependent and CD16-independent mechanisms (132,133).…”
Section: Monoclonal Antibodies For Targeting Plasma Cellsmentioning
confidence: 99%
“…SLAMF7 engages with itself as a ligand and is highly expressed on both NK cells and MM cells [ 10 ]. We have previously shown that coordinate SLAMF7 expression on both NK cells and myeloma target cells significantly enhances natural cytotoxicity responses, since SLAMF7 is a co-stimulatory receptor in NK cells [ 51 ]. Here, we found substantially higher SLAMF7 levels on NK cells in BM, as compared to peripheral blood, in nearly all ND, RR, and pSCT patients, and the SLAMF7 expression levels on CD56 bright NK cells in the BM of most MM patients was higher than in the BM of three healthy controls ( Figure 2 F).…”
Section: Discussionmentioning
confidence: 99%
“…Since these patients received standard of care therapy, it is not known if SLAMF7 expression on NK cells would retain the same prognostic value for patients treated with the SLAMF7-targeting antibody elotuzumab. Therefore, it may be worthwhile to explore if ND patients with high SLAMF7 expression on NK cells are more responsive to treatment with elotuzumab, which stimulates the antibody-dependent killing of myeloma target cells by NK cells and monocytes and promotes the SLAMF7–SLAMF7-dependent co-stimulation of NK cells [ 10 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pazina et al demonstrated that elotuzumab increased NKG2D level in SKOV cells, which was a human ovarian cancer cell line, and expressed SLAM family member 7. Elotuzumab enhanced NK cytotoxicity to myeloma cells in an independent CD16 expression manner when the expression level of NKG2D was high on NK cells . On the contrary, daratumumab decreases the number of NK cells in patients with RRMM .…”
Section: Discussionmentioning
confidence: 99%